Pengaruh Pengembangan Karir Dan Kepuasan Kerja Terhadap Produktivitas Kerja Pada PT Santino Kabupaten Tangerang - Eva Augulin; Styo Budi Utomo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of career development and job satisfaction on work productivity at PT Santino, Tangerang Regency, both partially and simultaneously. This research method uses a quantitative method with a sample of 65 respondents, data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, determination coefficient analysis test, t test and f test. Based on the results of the t test, the calculated t is 5.547>1.998 and the significance value for the career development variable (X1) is 0.000, a significant value smaller than the probability value of 0.05 or 0.000<,05, meaning that the career development variable (X1) has a positive and significant effect on the work productivity variable (Y). at PT Santino. Based on the results of the t test, the calculated t value is 6.855>1.998 and the significance value for the job satisfaction variable (X2) is 0.000, the significance value is smaller than the probability value of 0.05 or 0.000<0.05, meaning that the job satisfaction variable (X2) has a positive and significant effect on the work productivity variable (Y). at PT Santino. Based on the results of the f test, the calculated f value is 27.825>3.15 and the significance value is 0.000<0.05. So, it can be concluded that the career development variables (X1) and job satisfaction (X2) simultaneously have a positive and significant effect on work productivity (Y). at PT Santino.